Pergeseran Penggunaan Bahasa Singkil Pada Anak-Anak Di Desa Danau Bungara: Indonesia - Marisa; Idaryani; Teuku Azhari (Journal of Practice Learning and Educational Development, 2026)
This research aims to describe the occurrence of language shift in Singkil among children in Danau Bungara Village, Kota Baharu Sub-district, Aceh Singkil Regency. The method used in this study is a qualitative research method conducted to provide an actual description of the occurrence of language shift in Singkil among children in Danau Bungara Village. The data collection techniques used in this study are observation and interviews. The data analysis used includes data reduction, data presentation, and conclusion drawing. This research focuses on three domains: the family domain, the environment domain, the school domain, and the factors that cause the language shift. Based on research findings, it shows that in the family domain, the majority of children use Bahasa Indonesia when interacting with family members such as parents, siblings, and other relatives. In the children's environment, they predominantly use Bahasa Indonesia rather than Singkil, whether they are playing with peers or communicating with those around them. In the school domain, children use Bahasa Indonesia overall. These findings prove that there has been a language shift from Singkil in the family, environment, and school domains. The factors causing the shift from Singkil include school or educational factors, family habits, environmental factors, and parental or children's attitudes towards the Singkil language.